Oswaldo de Souza: uma abordagem semiológico musical de suas canções à performance da canção de câmara brasileira - John Kennedy Pereira de Castro (2017)
Based on the semiological musical approach and aspects of phenomenology, our research deals with the Oswaldo de Souza (1904-1995) songs and aims to help in choices for performance based on the perception of possible dialogues that the work can establish with the interpreter and with the audience. The main objective of this research is, therefore, to point out ways that help the musical interpreter to recognize and understand the meanings that permeate the Brazilian chamber song, especially the regional one, in its multiple interactions for the construction of meaning, aiming at its updated performance. The work considers that such an understanding can lead to a successful performance and to the appreciation of this vocal chamber music genre. In order to study the works from the point of view of the musical semiology, we chose, as corpus for the study, a selected set of 16 songs by Oswaldo de Souza to be performed and, from among these, four to be studied under the parameters of the tripartite semiological conception by Jean Molino and Jean-Jacques Nattiez and propositions by Gaston Bachelard's phenomenology. From the analytical observation of such works, according to their poietic, immanent and aesthetic dimensions, as well as from the esponses expressed in a structured interview in which the participants listened to a selection of a set of Brazilian chamber songs of regional character, it was sought to explore and establish possible dialogues with the audience and the contemporary Brazilian interpreter for the current understanding, diffusion and survival of the work. We also approach the songs regarding the relations between poem and music, drawing from this approach interpretative indications based on the characteristics related to the telluric to which the composer reports in his poietic process. We conclude our thesis by defending the aesthetic dimension of the musical semiology developed by Nattiez as a contemporary parameter for performance from which we can obtain a series of answers to the current interpretative questions and to the imagistic ideals pointed out by the contemporary public in the constant dynamics of the survival of these musical works in the course of time.